2018
DOI: 10.3390/cryst8080319
|View full text |Cite
|
Sign up to set email alerts
|

Structural Chemistry of Halide including Thallides A8Tl11X1−n (A = K, Rb, Cs; X = Cl, Br; n = 0.1–0.9)

Abstract: A8Tl11 (A = alkali metal) compounds have been known since the investigations of Corbett et al. in 1995 and are still a matter of current discussions as the compound includes one extra electron referred to the charge of the Tl117− cluster. Attempts to substitute this additional electron by incorporation of a halide atom succeeded in the preparation of single crystals for the lightest triel homologue of the group, Cs8Ga11Cl, and powder diffraction experiments for the heavier homologues also suggested the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…For example, K 49 Tl 108 is only known for potassium, whereas at a similar VEC A 15 Tl 27 (A = Rb, Cs) is reported. The question arises, if the compounds K 15 Tl 27 or Rb 49 Tl 108 exist or if the formed structure type is unique for potassium respectively rubidium/cesium. An approach could be the employment of mixed alkali metals in order to prove, if there are site preferences and if yes, which alkali metal on which site is essential for structure formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, K 49 Tl 108 is only known for potassium, whereas at a similar VEC A 15 Tl 27 (A = Rb, Cs) is reported. The question arises, if the compounds K 15 Tl 27 or Rb 49 Tl 108 exist or if the formed structure type is unique for potassium respectively rubidium/cesium. An approach could be the employment of mixed alkali metals in order to prove, if there are site preferences and if yes, which alkali metal on which site is essential for structure formation.…”
Section: Discussionmentioning
confidence: 99%
“…The anionic moiety is represented by a Tl11 cluster, but in contrast to their highest possible symmetry (D3h in A15Tl27; see Section 3.2), here only D3 symmetry for the Tl11 unit is realized, according to their site symmetry. The substitution of the extra electron in A8Tl11 by halide results in A8Tl11X, in which a less degree of distortion of the Tl11 7− cluster is observed, electronic effects of the extra electron therefore cannot be excluded [49]. Due to the high symmetry of the crystal structure, only two The possibility of an ordered substitution of Rb4 by the largest alkali metal cesium was shown for the compound Rb 14 CsTl 27 [35].…”
Section: A8tl11 (A = K Rb Cs)mentioning
confidence: 99%
See 1 more Smart Citation
“…This extra electron can be replaced by halide in A 8 Tr 11 X, and for Cs 8 Ga 11 Cl diamagnetic behavior is observed [16][17][18][19]. Detailed investigations on A 8 Tl 11 X showed that this replacement is accompanied by a less pronounced distortion of the Tl 11 clusters from ideal D 3h symmetry [17,18]. In general, Tl 11 7clusters represent a favored geometry as they also can be perceived as doubletetrahedral star units, which represent a very common structural motif in intermetallic compounds [20].…”
Section: Introductionmentioning
confidence: 98%
“…In these compounds, an extra electron is present A 8 [Tr 11 7-][e -] being responsible for pauli paramagnetism and metallic behavior. This extra electron can be replaced by halide in A 8 Tr 11 X, and for Cs 8 Ga 11 Cl diamagnetic behavior is observed [16][17][18][19]. Detailed investigations on A 8 Tl 11 X showed that this replacement is accompanied by a less pronounced distortion of the Tl 11 clusters from ideal D 3h symmetry [17,18].…”
Section: Introductionmentioning
confidence: 99%